Laser Performance of Nd-Doped Fiber Laser at 1120 nm - Zhiquan Lin; Yan Feng; Dijun Chen; Weibiao Chen (IEEE Photonics Journal, 2022)
Compared with Yb, Nd has potential in 1120 nm fiber lasers, with the characteristics of larger emission cross section and four-level structure. In this work, Nd-doped fiber (NDF) oscillator and Nd-Raman fiber (NRF) oscillator were built using single-mode 5/125 NDF to study the lasing characteristics at 1120 nm, especially the suppression of amplified spontaneous emission at 1060 nm. Limited by the parasitic oscillation at 1060 nm, the NDF oscillator achieved 5 W output at 1120 nm. The NRF oscillator removed the limitation due to the Raman shift from 1064 nm to 1120 nm and obtained an output of 7.7 W at 1120 nm with a spectral peak-to-peak contrast of 36 dB. This work provides experimental basis for the application of NDF in 1.1 μm.